Lithostratigraphy, facies, mineralogy and diagenesis of the syntectonic late Oligocene and Neogene Barzaman Formation (Al-Khod, Sultanate of Oman). (January 2022) - Mattern, Frank; Al-Amri, Shaima; Scharf, Andreas; Al-Sayigh, Abdul Razak; Farfour, Mohammed; Pracejus, Bernhard; Al-Omairi, Juhaina; Callegari, Ivan; Abbasi, Iftikhar
Abstract: This is the first comprehensive study of the >170-m-thick late Oligocene to Pliocene(?) Barzaman Formation from the northern side of the Oman Mountains. Our work closes a major gap in the understanding of a complex geological interval and region which was affected by regional doming, syndepositional thrusting, changing eustatic sea level and changing climate. The dynamic, and diverse setting is reflected by the formationʼs varied lithologies. Based on seven measured sections we subdivided the Barzaman Formation into five lithostratigraphic units which we correlated over a distance of 1.3 km. The lower three units are shallow marine, the remaining two units are terrestrial. The marine development was at first siliciclastic (near-shore; Unit 1), followed by coral limestone deposition with some associated siliciclastics (Unit 2) and then siliciclastic again (Unit 3). The limestones include a coral-bearing limestone debrite. Associated (or at least contemporary) with the debris flow, are coral limestone boulders which rolled downslope beyond the area of limestone deposition. The lower terrestrial unit (Unit 4) is marked by isolated lenticular claystone beds within weathered conglomerates. The claystone beds, which may be cellular, consist of palygorskite and commonly also of saponite. Their clay mineralogy, limited areal extend and association with conglomerates indicate their origin from evaporation of small ponds/pools between wadi gravel. Within the claystones and conglomerates, two slides were identified. These slides and the limestone debrite indicate slope instability which we attribute to syndepositional thrusting. Thrust deformation may explain the thickness variations of units 2–4. The uppermost Unit 5 is characterized by highly altered conglomerates whose primary features are largely obliterated by diagenesis such as (1) alteration and replacement of igneous ophiolite clasts, (2) local basal silica cementation and (3) mainly dolomite cement with some calcite cement. Based on the general geological setting (doming, falling eustatic sea level) and the involved near-surface diagenetic processes we interpret these conglomerates as terrestrial. Diagenesis of Unit 5 indicates an increasingly wet climate. Considering the foraminifer-constrained age of Unit 2, paleostress constraints and dated climatic change data, we conclude that the Barzaman Formation dates as late Oligocene to at least the mid-Miocene. Highlights: The Barzaman Fm. comprises sandstone, conglomerate, limestone and claystone. The formation formed in shallow marine and terrestrial environments. Some terrestrial evaporation took place. Deposition ensued during changing climate and eustatic sea-level. Deposition occurred during regional doming and thrusting. Near-surface diagenesis intensely modified the late terrestrial conglomerates.